RELATIONSHIP BETWEEN NURSING AND ELDERLY CARE STUDENTS’ ATTITUDES TOWARDS AGEISM - Merve Çayir Yilmaz; Fatma Zehra Ince (Belitung Raya Foundation, Indonesia, 2017)
Background: Perceptions of individuals and society about the elderly are reflected in the services provided to them. These reflections might be revealed in various fields such as health care services and sufficient job opportunities, or they could be revealed in the issue of discrimination against the elderly, which is a problem emerging in advanced ages. Objective: This study aims to identify the relationship between nursing and elderly care program students’ attitudes towards ageism. Methods: This study, which is descriptive and relational method, was conducted between November and December, 2016. The participants were 220 students. The data were collected through a questionnaire, and the Ageism Attitude Scale, and were analyzed using t-test, two-way multivariate analysis of variance (MANOVA) and one-way analysis of variance (ANOVA). Findings: Results show that the students generally had positive attitudes towards ageism. Nursing department students received significantly higher scores in the Limiting the Elderly Person’s Life sub-dimension and Ageism Attitude Scale in comparison to Elderly Care Program students. 3rd year nursing department students had higher scores in the Ageism Attitudes Scale in comparison to 1st and 2nd year nursing department students and students in the Elderly Care Program. “Positive Discrimination towards the Elderly” sub-dimension and the “Ageism Attitudes Scale” total scores were found to be significantly higher in nursing department students according to the variable of desire to work in a geriatric service in the future. (p<0.05). Conclusion: This study found that students had positive attitudes towards ageism, and nursing students’ Ageism Attitudes Scale mean scores were higher than those of elderly care program students. More comprehensive studies are needed in order to improve students’ attitudes towards elderly people.